Socio Economic Evaluation of Human Wildlife Conflict Management - a Case Study from Uttarakhand, India - Mishra, B. K.; Maniktala, Rupashi (Indian Forester, 2011)
The role of community in the management of human-wildlife conflicts, although recognized, has neither been adequately evaluated nor clearly documented. Therefore net economic loss was evaluated due to crop depredation in a PA neighboring village of Uttarakhand, capital cost of a power fence to deter wildlife entering the crop fields and recurring cost of maintenance, and cost of crop protection. Net amount society is willing to pay for maintenance of power fence was estimated 19200 per year, whereas actual amount required was 11500. Authors compared the cost of power fence with monetary value of crop loss and estimated that the cost of fence can be recovered in just 1.26 years. The analysis revealed that the perceived benefits from power fence were much higher than the cost borne by farmers due to crop depredation suggesting the critical role of community not only taking responsibility of maintenance, but also bearing the initial cost of fence. This study also revealed a higher level of tolerance of local people towards crop raiding wildlife- a strong factor in favour of forging partnership with them in managing human-wildlife conflict.